Penerapan Metode Wahdah Dalam Meningkatkan Hafalan Al-Qur’an Siswi Asrama Tahfidz MAN 2 Langkat - Muammar Al Qadri; Avif Ilhamsyah (Fakultas Syariah IAIN Laa Roiba Bogor, 2020)
The Wahdah method is a method of memorizing the Qur'an by reciting one by one the verses that will be memorized repeatedly. Not a few of the students complained about the difficulty of memorizing the Qur'an, it was due to the large number of students who did not know about the methods that could be used in memorizing the Qur'an. In order to memorize the Qur'an becomes lighter, of course as a student must understand the methods that can be applied in memorizing. This research is a qualitative descriptive study which was carried out on the Tahfidz Dormitory students of MAN 2 Langkat. The sources of research data in this study are the results of observations, documentation and interviews with research informants. The findings of this study indicate that the majority of students apply the wahdah method in improving their memorization. Many students do not know the name of the method they use in memorizing the Qur'an, through this interview they reveal their way of memorizing after which the researcher concludes. The students apply this method because they find it easy with the method it uses. The application of the Wahdah Method in the Tahfidz Dormitory of MAN 2 Langkat greatly affects the memorization of the Qur'an of the Tahfidz Dormitory students. The implementation of the wahdah method begins with improving the reading, then after the reading is good enough, it is continued by memorizing one verse by one until it reaches one page. After that the memorization is deposited to the supervisor or teacher. The memorization of the Qur'an of the Tahfidz Dormitory MAN 2 Langkat students increased after the use of the wahdah method. Students find it easier to memorize the Qur'an..